White Color in Traditional Worldviews of Tuvans and Buryats: Semantics and Associative Thesaurus Approached - Galina A. Dyrkheeva; Chechek S. Tsybenova (Монголоведение, 2022)
Introduction. The article examines results of associative experiments with native speakers of Tuvan and Buryat to analyze the color term ‘white’. Goals. The paper attempts conceptual and semantic analyses of obtained associative fields in comparison to traditional cultural representations of Tuvans and Buryats. Materials and methods. The paper considers materials of associative experiments attended by native speakers of Tuvan and Buryat in different years. Results. The study reveals that associative meanings of the color terms ak and sagaan are largely constituted by semes common to nomadic culture and relating to milk, white ritual food, religious representations of white as a pure and sacred color. In the associative thesaurus of Tuvan and Buryat, white conveys predominantly light semantics and positive emotions, correlates with a wide range of objects and phenomena of the outer world. Like in lexicographic sources, no semantics associated with negative emotions have been traced. However, despite such concepts as ‘death’ and ‘passing away’ are not associated with white color, nor there are any linguistic mentions — this color is involved in corresponding customs and rites. The experimental materials also show meanings specific to both the Tuvan and Buryat linguocultures, which results from differing ethnocultural traditions and language structures. In Buryat, such discrepancies occur in reactions of religious contexts — Sagaalgan, Sagaan Ȕbgen. In Tuvan, those are toponyms, such as Ak-Turug, Ak-Khem, and the reaction kara that has broad functional meanings. The analysis also shows that many associative values coincide with main meanings of corresponding lexemes (reactions/superordinates unge(n) and on). Conclusions. The study confirms that cultural and historical similarity plays an important role, and many ethnocultural stereotypes of native speakers of related languages have more conformities than differences.